Access network evolution beyond third generation mobile communications. - Mohr, W. (IEEE Communications magazine)
Second-generation mobile radio systems have been deployed successfully worldwide. These systems have evolved to higher data rates and packet transmission. Third-generation mobile radio systems are currently being standardized worldwide to be initially deployed in 2001 and 2002 in different regions of the world. New advanced multimedia services are under development, and first services are already being offered in second-generation systems, which will provide new business opportunities. Already today discussion is starting on the development of systems beyond third-generation mobile radio systems due to the long timeframe for system specification and international standardization. However, today there is no clear vision available on such systems. This discussion takes into account the new deregulated and liberalized communication environment. This article presents a concept for a system beyond third-generation mobile radio systems, which comprises a combination of several optimized access systems in a common IP-based medium access and core network platform. These different access systems will interwork through horizontal and vertical handover, service negotiation, and global roaming. The different access systems are allocated to different mutually complementing cell layers in the sense of hierarchical cells with respect to cell size, coverage, and mobility to provide globally optimized seamless services to users. This vision requires extensive international research and standardization activities to solve many technical challenges. Key issues are the global interworking of different access systems on a common platform, advanced antenna concepts, and the implementation of multimode and multiband terminals and base stations through software-defined radio concepts.